Integrating Agro-Waste Fiber into Sustainable Textile Innovation: Characterization of Mechanically Extracted Pineapple Leaf Fiber (PALF) for Circular Composite Applications - Darmawi, Ahmad; Parmawati, Sih; Ikhsani, Nurfadilah; Fahad, Fahad (Universitas Sebelas Maret, 2026)
This study explores the potential of pineapple leaf fiber (PALF) from the Queen variety as a sustainable reinforcement material for green composites and textiles, focusing on the effects of mechanical retting. The research addresses critical barriers to industrial adoption, such as fiber-quality variability and hydrophilicity, while highlighting an innovative waterless extraction method that reduces environmental impact compared with conventional processes. A quantitative experimental approach was employed to comprehensively characterize PALF, incorporating standardized tensile testing to measure mechanical properties and microscopic analyses with a Scanning Electron Microscope (SEM) to observe fiber morphology. Findings demonstrate that mechanical retting significantly improves PALF’s tensile strength (23.2 g/tex) and fineness (33.7 dtex). Microscopic analysis reveals a uniform, compact fiber structure that underpins the material's enhanced mechanical performance. PALF emerges as a viable, eco-friendly alternative to synthetic fibers. The waterless mechanical retting process is an effective method for producing high-quality reinforcement fibers, offering practical guidance for industries. This approach contributes significantly to agricultural waste reduction and advances circular economy principles in sustainable materials development.